Expression of atherosclerosis-associated genes in peripheral blood of drug-naïve hypertensive subjects with newly-diagnosed type 2 diabetes mellitus - Nikolay Stoynev; Ivanka Dimova; Blaga Rukova; Savina Hadjidekova; Dragomira Nikolova; Tsvetalina Tankova (Pharmacia)
Aim: To evaluate the expression of atherosclerosis-associated genes in peripheral blood of drug-naïve hypertensive subjects with newly-diagnosed type 2 diabetes mellitus. Materials and methods: Eighteen subjects (15 males, 3 females), mean age 46.27 ± 12.07 years, divided into two groups: studied group - subjects with newly-diagnosed hypertension and newly-diagnosed type 2 diabetes (n = 9), control group – normotensive individuals with newly-diagnosed type 2 diabetes (n = 9) Gene expression analysis was performed with Human Atherosclerosis RT2 Profiler PCR Array. Results: In gene expression analysis, 5 genes with increased expression in the studied group were found – CD44, ITGA5, ITGB2, PPARA and RXRA. No genes with decreased expression matching the criteria were found. Conclusion: The presence of arterial hypertension in subjects with newly diagnosed type 2 diabetes tends to increase the expression of CD44, ITGA5, ITGB2, PPARA and RXRA in the peripheral blood.